2021
DOI: 10.1088/1755-1315/650/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Introgession of powdery mildew resistance into cultural pea from wild accession of P. fulvum

Abstract: Wildlife pea specimen P. fulvum i-609881 of the UIP collection (Saint Petersburg, Russia) in a greenhouse box has demonstrated full resistance to powdery mildew. As a result of crossing with cultivated peas, interspecific hybrids of Stabil × i-6098881 were obtained. In populations of interspecific hybrids, the BC2F3 Stabil × i-609881 line of the leafless morphotype (af), resistant to the powdery mildew pathogen, was isolated as a result of backcrossing. As a result of crossing plants of this line with suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Studies on the inheritance of PM disease revealed three genes, namely er1, er2 and Er3, conferring resistance to Erysiphe species [22], (Figure 2). An investigation into the genetics of powdery mildew resistance (PMR) has been carried out in the past, which has shown different modes of inheritance including single recessive [35,36], single dominant [9,37] and duplicate recessive gene actions [38,39] (Table 2). Hammarlund [19] was the first to investigate PM resistance in peas and reported cumulative factors for susceptibility.…”
Section: Geneticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies on the inheritance of PM disease revealed three genes, namely er1, er2 and Er3, conferring resistance to Erysiphe species [22], (Figure 2). An investigation into the genetics of powdery mildew resistance (PMR) has been carried out in the past, which has shown different modes of inheritance including single recessive [35,36], single dominant [9,37] and duplicate recessive gene actions [38,39] (Table 2). Hammarlund [19] was the first to investigate PM resistance in peas and reported cumulative factors for susceptibility.…”
Section: Geneticsmentioning
confidence: 99%
“…P. fulvum is a wild Pisum species that has little hybridization success with P. sativum and is likely to suffer from linkage drag [127]. However, other researchers have successfully utilized this species to transfer the PM resistance into the cultivated genotypes [37,49,118].…”
Section: Molecular Breeding Using Linked Dna Markersmentioning
confidence: 99%
See 3 more Smart Citations